2007
DOI: 10.1038/sj.npp.1301586
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Pharmacological Validation of the Gerbil Forced-Swim Test: Effects of Neurokinin-1 Receptor Antagonists

Abstract: Several studies have suggested that neurokinin-1 (NK1) receptor antagonists may have therapeutic potential as novel antidepressant drugs. To test these compounds preclinically, gerbils have become one of the preferred species in that they demonstrate close NK1 receptor homology with humans and bind NK1 antagonists with higher affinity than rats and mice. The intent of the present study was to determine whether the forced-swim test (FST), one of the most commonly used animal tests of antidepressant-like activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…The doses used were also in a similar range to those published in our previous behavioral studies using monoamine reuptake inhibitors (Robinson, 2012; Humpston et al , 2013). Doses for agomelatine (Bourin et al , 2004), aprepitant (Wallace-Boone et al , 2007), FG7142 (Rogers et al , 1995), rimonabant (Tzavara et al , 2003), and 13-cis-retinoic acid (Ferguson et al , 2005; O'Reilly et al , 2006) were based on previous studies in rodents. Doses used for diazepam were based on previous studies showing anxiolytic effects in other animal models (Wieland and Lucki, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…The doses used were also in a similar range to those published in our previous behavioral studies using monoamine reuptake inhibitors (Robinson, 2012; Humpston et al , 2013). Doses for agomelatine (Bourin et al , 2004), aprepitant (Wallace-Boone et al , 2007), FG7142 (Rogers et al , 1995), rimonabant (Tzavara et al , 2003), and 13-cis-retinoic acid (Ferguson et al , 2005; O'Reilly et al , 2006) were based on previous studies in rodents. Doses used for diazepam were based on previous studies showing anxiolytic effects in other animal models (Wieland and Lucki, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…However, in another clinical trial, a lack of efficacy of aprepitant (Table 1) has been reported in the treatment of major depression (Keller et al 2006). It is also known that oral administration of NK-1 receptor antagonists (aprepitant, L-733,060, CP-122,721) ( Table 1) produces anxiolytic-like effects in the gerbil elevated plus-maze, and NK-1 antagonists reduce immobility in the gerbil forced-swim test without affecting locomotor activity (Wallace-Boone et al 2008). This is important, since it is known that the gerbil NK-1 receptor is similar in homology to the human NK-1 receptor.…”
Section: Emotional Stress (Anxiety and Depression)mentioning
confidence: 97%
“…106 NKR-1 is a receptor for substance P, an important itch mediator. 110113 NKR-1 antagonists were found to also have effects in modulating mood disorders: vestipitant is under development as a potential anxiolytic and possibly antidepressant agent, 114 and L-733,060 (Merck Sharp & Dohme, New Jersey, United States) was shown to have antidepressant 115,116 and anxiolytic 117 effects in animal studies. Aprepitant, though, was found not to be efficacious in treating major depressive disorder in clinical trials 118 and plans to market it as an antidepressant have since been abandoned.…”
Section: Management Of Psychosomatic Factorsmentioning
confidence: 99%